Conceptualization of medication, life and death: Religio-scientific approach - Ahmed Shogar, Ibrahim Adam (2010)
Medicine and medication are aspects of philosophy of life and death. Why we get sick, why we take medicine and why we die? Every nation answers these questions in the framework of its own worldview: from where we come, why we are here in this turbulence world, and where we are gone? This mode of questions has no cure in medicine: they are the ultimate questions of mankind throughout the history. The way you answer these questions provides guiding principles and clues to your health system. In the other words, the conceptualization of medication system is an integral part of way of interpreting the origin og life, its meaning and purpose. These are the basic problems of human intellect throughout the history. Mankind has been trying to find proper answers to these questions by various means. The scientific investigation, philosophical speculation, and religious teaching are the basic approaches to find solution to the problems. Many of traditional methods in medication were mainly based on tow sources: religious beliefs and mere practices. The modern biology describes the therapeutic methods and medication based on its own concept of life. But biological meaning of life does not reflect all the fact about human aspects: mental, spiritual, and physical. The concept of life is deeply controversial issue according to religion, philosophy and modern physics. For instance Einstein's theory of relativity of space-time incredibly asserts that the length of a time interval-the age one lives-depends on one's speed. Meaning that the faster we move the longer we appear to live to someone who is not moving with us. The faster elements take longer to die, the slower ones die early. Einstein's ideas have brought about a revolution in the physicist's thinking. The modern developments in genetic and DNA research obviously create more complicated situation about conceptualization of life and death, and accordingly about therapeutic methods. The direct implication of scientific developments is that it has discovered our need to multidimensional approach of science, region and philosophy, rather than a single therapeutic method. The central point of this work is to highlight the concept of life and death from the perspectives of both religion and science and its role in conceptualization medication.